Types and anatomical locations of injuries among mountain bikers and hikers: A systematic review - Paul John Braybrook; Hideo Tohira; Tanya Birnie; Deon Brink; Judith Finn; Peter Buzzacott (PLoS ONE, 2023)
Background Mountain biking and hiking continue to grow in popularity. With new participants to these sports, it is likely the number of injuries will increase. To assist medical personnel in the management of these patients we attempted to quantify the types and locations of injuries sustained by mountain bikers and hikers. Objective The objective of this systematic review is to identify the type and anatomical location of injuries for both mountain bikers and hikers. Methods A systematic search was undertaken using CINAHL, Cochrane, ProQuest, PubMed and Scopus databases. Reviewers assessed the eligibility of articles by a title/abstract review and final full-text review. Studies were included if the types of injuries were reported by medical personnel and contained anatomical locations. Studies were excluded if it did not take place on a trail or if the injuries were self-reported. Risk of bias was assessed utilising the Joanna Briggs Institute (JBI) checklists for study quality. No meta-analysis or comparison between mountain bikers and hikers was possible due to the high heterogeneity of the definition of injury. Results A total of 24 studies met the inclusion criteria, 17 covering mountain biking and 7 hiking. This represented 220,935 injured mountain bikers and 17,757 injured hikers. The most common type of injuries sustained by mountain bikers included contusions, abrasions and minor lacerations, which made up between 45–74% of reported injuries in studies on competitive racing and 8–67% in non-competitive studies. Fractures represented between 1.5–43% of all reported injuries. The most injured region was the upper limbs reported in 10 of 17 studies. For hikers the most common injuries included blisters and ankle sprains with blisters representing 8–33% of all reported injuries. The most common body location to be injured by hikers was a lower limb in all 7 studies. Conclusions This is the first systematic review to report on the injury epidemiology of the two most common trail users; mountain bikers and hikers. For participants in both activities the majority of injuries were of minor severity. Despite this, the high proportions of upper limb fractures in mountain bikers and ankle sprains in hikers cannot be ignored. Trial registration Registration: This systematic review was prospectively registered with the University of York PROSPERO database on the 12/4/2021 (CRD42021229623) https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021229623.